Transactional Clinical Support For Mutual Aid Groups: Toward A Theory Of Transactional Movement Lawyering - Michael L. Haber (Washington University Journal of Law and Policy, 2022)
The COVID-19 pandemic has had a tremendous influence on our communities. The implications of the pandemic have led to the creation of thousands of “mutual aid” projects. This Article tells the story of these groups through the work of the Hofstra Law School Community Economic Development (“CED”) Clinic. Haber describes the work the CED has done to provide legal support and information to hundreds of COVID-19 mutual aid projects. The Article also briefly reviews Professor Dean Spade’s 2020 book, Mutual Aid: Building Solidarity During This Crisis (and the Next), contrasting it with a legal guide for mutual aid groups written by the author. Haber concludes by describing mutual aid work in the context of recent scholarship on “movement lawyering,” arguing that community economic development lawyers could deepen their impact through a meaningful engagement with movement lawyering principles.
Keywords: COVID-19 Pandemic; Mutual Aid Projects; Movement Lawyering